Effect of uterine massage and emptying of the urinary bladder on alleviation of afterpains among mothers in the immediate postpartum period - Sabah Lotfy Mohamed El Sayed (Elsevier, 2021)
Background: Afterpains are the most common complaint after a normal vaginal delivery. Non-pharmacological techniques are important priority care for alleviating afterpains. Aim: The present study aimed to assess the effect of uterine massage and emptying of the urinary bladder on alleviation of afterpains among mothers in the immediate postpartum period. Subjects and method: In the quasi-experimental study design, 88 mothers who had afterpains were selected by purposive sampling from the postpartum ward of Zagazig University Hospital, Egypt. Data were collected through a structured interview sheet and visual analog pain scale. The study sample received a uterine massage and regular emptying of the urinary bladder. The outcome (afterpains) was assessed using a visual analog pain scale after an hour of childbirth until discharge from the hospital. Results: There was a significant reduction in the level and mean afterpains score after the interventions (P = 0.012 & P < 0.000), respectively. Conclusion: The study concluded that uterine massage and regular emptying of the urinary bladder were effective in reducing the level of afterpains among mothers in the early postpartum period. Mothers should be encouraged to use these methods as alternative techniques to relieve afterpains and overcome the side effects of using analgesics.